Pioneers in Housing : An Oral History Project oral history interviews - Schussheim, Morton J.; Cole, Albert M., 1901-; Klutznick, Philip M., 1907-; Rouse, James W.; Weaver, Robert C. (Robert Clifton), 1907-1997; Woodbury, Coleman, 1903-1994.
Transcripts of oral history interviews conducted by Schussheim with community developers, educators in urban studies, and officials in the Department of Housing and Urban Development and its predecessor, the Housing and Home Finance Agency. Interviewees discussing the development of public housing and community planning include Albert M. Cole, Philip M. Klutznick, James W. Rouse, Robert Clifton Weaver, and Coleman Woodbury.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Senior specialist in housing, Congressional Research Service, Library of Congress.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: United States. -- Department of Housing and Urban Development; United States. -- Housing and Home Finance Agency; Community development, Urban; Housing policy; Public housing